Cellular homeostasis, implantation window and unexplained infertility: role of phosphatase and tensin homolog deleted on chromosome 10 - Makker, Annu; Goel, Madhu Mati; Manu, Kumari; Makker, Renu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Balance between endometrial cell proliferation and apoptosis is crucial for successful embryo implantation. PTEN (phosphatase and tensin homolog deleted on chromosome 10), a pro-apoptotic factor, is proposed to be one of the signaling proteins through which estrogen and progesterone act to affect cellular homeostasis. Although reports in literature have suggested role of PTEN in regulating endometrial cell proliferation and apoptosis during window of implantation, its involvement in women with unexplained infertility is not clear. In the present study, we examined expression, cellular distribution and activation status of PTEN, cell proliferation, and apoptosis in midsecretory endometrium from women with unexplained infertility as compared to fertile controls. Methods: Endometrial biopsies from infertile (n=11) and fertile women (n=22) were used for immunohistochemical evaluation of PTEN, phospho-PTEN and Ki67. Terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate nick end labeling assay was performed for detection of apoptotic cells. Results: Biopsies from infertile women as compared to fertile controls demonstrated statistically significant: i) decrease in nuclear PTEN (P < 0.001), increase in nuclear phospho-PTEN (P < 0.05), increase in nuclear and cytoplasmic phospho-PTEN/PTEN ratio (P < 0.001 and P < 0.05 respectively) in endometrial stroma, ii) increase in cytoplasmic phospho-PTEN (P < 0.001) and phospho-PTEN/PTEN ratio (P < 0.05) in glandular epithelium (GE), iii) increase in Ki67 labeling in GE (P < 0.01) and stroma (P < 0.05) and, iv) decrease in (P < 0.001) apoptosis. Conclusions: Altered PTEN expression and associated modulation in cellular homeostasis during the implantation window might contribute to mechanism underlying unexplained infertility.